EPISTIMOLOGI PENDIDIKAN: STUDI TENTANG HAKIKAT DAN TUJUAN PENDIDIKAN ISLAM DALAM AL-QUR’AN - Romadhon, Fathur Rohman; Hasyim, Muhammad Rafli; Bahir, Ahmad; Muhayar, Marhadi; Luthfi, Attabik (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
From an Islamic viewpoint, the epistemology of Islamic education is a philosophical examination of the nature of knowledge, how it is acquired, and the standards of truth. Islamic education is essential because it emphasizes pupils' moral growth, religious beliefs, and dedication in addition to scholastic achievement. This book intends to examine the epistemology, nature, and objectives of Islamic education in light of the Qur'an. This study, which employs a qualitative approach and a literature study technique, draws its data from books, scholarly articles, and other pertinent scientific journals, all of which are subjected to descriptive and analytical analysis. The study results support the conclusion that Islamic education's epistemology is founded on the integration of revelation and rationality's values in order to create a well-rounded person. The planned, systematic, and ongoing attempt to promote the balanced development of human physical and spiritual potential is what Islamic education is all about. Islamic education seeks to attain happiness in this world and the afterlife by portraying people as God's servants ('abdullah) and vicegerents on earth (khalifatullah). The verses of the Quran that were examined emphasize that the main objective of Islamic education is to please Allah, encourage obedience, promote reverence, and equip people for their social and humanitarian obligations. As a result, Islamic education is a comprehensive and integrated educational system that fosters the growth of cognitive, emotional, and psychomotor skills in accordance with Islamic principles.